"Hey, we also have something to say": A qualitative study of Portuguese adolescents' and young people's experiences under COVID‐19. Issue 8 (1st October 2020) - Branquinho, Cátia; Kelly, Colette; Arevalo, Lourdes C.; Santos, Anabela; Gaspar de Matos, Margarida
Abstract: Objective: (1) To give adolescents and youth a voice and listen to the impact of coronavirus disease 2019 (COVID‐19) in their lives; (2) to identify their coping strategies; (3) present lessons learned to be better prepared for future pandemics. Methods: Six hundred and seventeen participants from 16 to 24 years old (M = 19.2 years; F = 19.1 years) answered the online questionnaire during the pandemic lockdown. Sociodemographic data were analyzed with SPSS version 26 and qualitative data with MAXQDA 2020. Engel's Biopsychosocial model supported the analysis and data presentation. Results: in terms of impacts, stands out: biological —headaches and muscle pain; psychological —more time to perform pleasant and personal development activities, but more symptoms of depression, anxiety, and loneliness, longer screen time, and more substance use; social —increase of family conflicts and disagreements, loss of important life moments, contacts, and social skills, but it allows a greater selection of friendships. Regarding coping strategies, the importance of facing these times with a positive perspective, carrying out pleasurable activities, keeping in touch with family and friends, and establishing routines are emphasized. As lessons for future pandemics, the importance of respecting the norms of the Directorate‐General for Health, the need for the National Health System to be prepared, as well as teachers and students for online learning, and studying the possibility of establishing routines with the support of television. Conclusions: This study illustrates adolescents and young people's perception of the impacts of the pandemic upon them, as well as their competence to participate in the issues that directly affect them. Priorities to mitigate the impact of future pandemics are presented.